Effect of Different Silane Treatments on Long-Term Bonding Between Non-Etched Glass-Ceramic and Resin Cement - Murillo Gómez DDS, MSc, Fabián; De Goes DDS, MSc, PhD, Mario F. (Odovtos - International Journal of Dental Sciences, 2017)
The present study evaluated the bond strength between glass-ceramic and resin cement, using different silane treatments, performing no previous hydrofluoric acid (HF) etching on ceramic surface, after short- and long- term storage. One hundred and eighty glass-ceramic plaques (IPS e.max CAD®) were polished and divided into six groups (n=30) to receive different silane treatments: (1) RCP-RelyX Ceramic Primer® (one-bottle silane), (2) RCP+SB-RelyX Ceramic Primer and Adper Singlebond2® (silane plus separated adhesive), (3) SBU-Scotchbond Universal® (silane-containing universal adhesive), (4) CP-Clearfil Ceramic Primer® (silane/MDP primer), (5) NC-no-silane (negative control) and (6) PC-Previous HF etching (5%, 20s) plus RelyX Ceramic Primer® (positive control). Two resin cement cylinders (Rely X Ultimate®) were built on each plaque. Each group was divided into two sub-groups to be stored for 24 hours (24h) or 6 months (6mo) in distilled water at 37°C (n=15). Then microshear (µSBS) testing was performed. Failure mode was analyzed using scanning electron microscopy (SEM). Data were statistically analyzed by two-way ANOVA and Tukey´s test (α=0.05). Both factors and their interaction resulted statistically significant (p≤0.05). PC obtained the highest µSBS values (in MPa) at both storage times (24h: 28.11±2.44; 6mo: 19.10±3.85). After 24h storage, groups RCP+SB (10.86±3.62), SBU (8.37±4.33) and CP (8.05±3.62) were not statistically different from NC (8.00±2.51); only RCP (19.73±4.63) and PC obtained higher values. After 6 months, only PC showed higher values than NC (0.04±0.01). Cohesive failure in resin cement was more prevalent for RCP-24h and PC, while adhesive failure was more frequent among all other groups. Clinical relevance: None of the commercially available silane primers tested, improve long- term ceramic/cement bonding without performing HF etching on ceramic surface. Combination of HF acid and silane, remain as a gold standard treatment for glass-ceramic materials.